Correlation Of Birth Weight With Stunting In Babies Aged 6-24 Months - Nur Isriani Najamuddin; Masyitah Wahab (Jurnal Vocational Nursing Sciences (VNUS), 2020)
Background: Stunting is one indicator of chronic nutritional status that describes stunted growth due to long-term malnutrition. One of the causes of stunting in children is family and household factors, namely maternal factors and the home environment. Objective: The purpose of this study was to determine the relationship between birth weight and the incidence of stunting in infants aged 6-24 months Method: This research was conducted in an analytical descriptive manner, namely research that tried to explore how the health phenomenon occurred. The population in this study was a number of infants aged 6-24 months, namely 48 infants. Considering that at the time of the study, there were 15 infants who were unreachable and, not in place at the time of the study, while the researcher's time was very limited, so in this study the researcher used a sample of 33 6-24 month old baby. Result: from the analysis test results with Fisher's exact test, a significance value of 0.023 and an odds ratio of 18.75 was obtained. Conclusion: The conclusion of this study is that from 33 infants aged 6-24 months, there are 7 babies who are LBW and 4 babies who are stunted. There is no relationship between birth weight and the incidence of stunting in infants aged 6-24 months where LBW babies are 18 times more likely to experience stunting than babies born with normal birth weight.